The Influence of Promotion and Service Quality on the Competitive Advantage of Mobile Haircut Services - Fitri Aulina (Jurnal Inovasi Informatika dan Bisnis Digital (JIIBD), 2026)
This research addresses the demanding mobile service business model by examining how Promotional strategies and Service Quality standards impact Competitive Advantage. The study adopted a quantitative survey approach, gathering information from Mobile Haircut Service customers located in Bintang Bayu District. Analysis via Multiple Linear Regression indicated that Promotion and Service Quality jointly exhibit a positive and significant impact on the dependent variable. Crucially, the partial results highlight that Service Quality holds the largest influence. This suggests that to secure long-term competitiveness, mobile haircut service companies must prioritize the consistent enhancement of service quality and integrate it effectively with robust promotional activities that reach and retain customers.